Business Education and Portfolio Returns - Adam Altmejd; Thomas Jansson; Yigitcan Karabulut (Institute of Labor Economics (IZA), 2024)
Using university admission cutoffs that generate exogenous variation in college-major choices, we provide causal evidence that enrollment in a business or economics program leads individuals to invest significantly more in the stock market, earn higher portfolio returns, and ultimately accumulate higher levels of wealth later in life. Underlying these effects, beyond differences in risk-taking, innate ability, labor market outcomes, or scale effects, is the enhanced ability of business educated individuals to acquire and process economic information and make informed investment decisions. Early investments in financial literacy thus play an important role in generating higher returns that significantly alter individuals' life-cycle wealth profiles.
Keywords: G11; G51; G53; I26; 330; portfolio choice; financial literacy; portfolio returns; household wealth; returns to education; distribution of wealth